Derivados pirazolínicos inéditos causam antinocicepção em camundongos no teste da formalina - Sauzem, Patricia Dutra (2004)
The discovery of pyrazole derivatives dates back to 1884, when the German chemist Ludwig Knorr attempted to synthesize quinoline derivatives with antipyretic activity and accidentally obtained antipyrine, a pyrazolinone, which has analgesic, antipyretic and antirheumatic activity. Since then, new pyrazole compounds, like phenylbutazone and dipyrone, were discovered. Dipyrone, probably the most widely studied pyrazole derivative, present analgesic, antipyretic and few antiinflammatory activities. The mechanism of action of pyrazole compounds seems to involve the central and peripheral inhibition of cyclooxygenase, a key enzyme in the synthesis of prostaglandin. In this work we studied the antinociceptive and antiinflammatory effects of a novel pyrazole-derived compounds: 4-methyl-5-hydroxy-5-trifloromethyl-4,5-diidro-1H-1-pyrazolcarboxyamide (NF0) and its related compound 3- methyl-5-hydroxy-5-trifloromethyl-4,5-diidro-1H-1-pyrazolcarboxyamide (NF2). The antinociceptive potential was assessed using abdominal writhing, hot plate and formalin tests in adult mice. Antiinflammatory activity was assessed by paw plethysmometry in adult rats using the carrageenin-induced paw edema test. Subcutaneous administration of NF0 (30, 100, 300 and 1000 μmol/kg) decreased time spent licking or biting the injected paw in the neurogenic phase of the formalin test. However, only 300 and 1000 μmol/kg NF0 decreased licking time in the inflammatory phase of the formalin test. On the other hand, subcutaneous administration of NF2 had no effect on licking time during the neurogenic phase, but decreased licking time in inflammatory phase of the formalin test at dose of 1000 μmol/kg. Naloxone (2,75 μmol/kg) pre-administration did not prevent NF0 and NF2-induced antinociception, suggesting that opioid mechanisms may not underlie such effects. NF0 and NF2 were devoid of antiinflammatory activity in the paw edema test in rats, and had no effect on the spontaneous locomotor activity and motor performance of mice in the rotarod test. These results suggest that NF0 induces antinociception in the neurogenic and inflammatory phases of the formalin test, while NF2 causes antinociception only inflammatory phase. Interestingly, the only difference between these compounds is the position of a methyl group in the pyrazole ring. In NF0, the methyl group is placed at position 4 of the pyrazole ring, while NF2 has such a methyl group positioned at the position 3. These results suggest an important structure-activity relationship for the antinociceptive effect these compounds.